COVID-19 Changed the Injury Patterns of Hospitalized Patients. Issue 3 (1st June 2021) - Rozenfeld, Michael; Peleg, Kobi; Givon, Adi; Bala, Miklosh; Shaked, Gad; Bahouth, Hany; Bodas, Moran
Abstract: Introduction: Injury patterns are closely related to changes in behavior. Pandemics and measures undertaken against them may cause changes in behavior; therefore, changes in injury patterns during the coronavirus disease 2019 (COVID-19) outbreak can be expected when compared to the parallel period in previous years. Study Objective: The aim of this study was to compare injury-related hospitalization patterns during the overall national lockdown period with parallel periods of previous years. Methods: A retrospective study was completed of all patients hospitalized from March 15 through April 30, for years 2016-2020. Data were obtained from 21 hospitals included in the national trauma registry during the study years. Clinical, demographic, and circumstantial parameters were compared amongst the years of the study. Results: The overall volume of injured patients significantly decreased during the lockdown period of the COVID-19 outbreak, with the greatest decrease registered for road traffic collisions (RTCs). Patients' sex and ethnic compositions did not change, but a smaller proportion of children were hospitalized during the outbreak. Many more injuries were sustained at home during the outbreak, with proportions of injuries in all other localities significantly decreased. Injuries sustained during the COVID-19 outbreak were more severe, specifically due to an increase in severe injuries in RTCs and falls. The proportion of intensive care unit (ICU) hospitalizations did not change, however more surgeries were performed; patients stayed less days in hospital. Conclusions: The lockdown period of the COVID-19 outbreak led to a significant decrease in number of patients hospitalized due to trauma as compared to parallel periods of previous years. Nevertheless, trauma remains a major health care concern even during periods of high-impact disease outbreaks, in particular due to increased proportion of severe injuries and surgeries.